Effects of COVID-19 Severity on Serum Calcium Levels - Umbreen Aslam, Muhammad Kashif Bashir, Nosheen Zafar, Niamat Ali, Salman Javed, Najam-us-Sehar Saeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The hypocalcaemia may be a unique biochemical feature of COVID -19 that has the potential to influence disease severity and represents a new potential therapeutic target worth testing in this clinical setting. Because COVID -19 testing has primarily focused on individuals with respiratory symptoms rather than calcium levels, Therefore the objective of current study was to determine the effect of e COVID-19 severity on Serum calcium levels. Methods: After the ethical approval, all the RT-PCR positive patients from the record of corona isolation wards of Ganga Ram hospital Lahore. Demographic details including name, age, gender, complete history & examination serum Calcium level was noted recorded al from hospital files on a predesigned proforma. To assess clinical severity of coronavirus disease, all the enrolled patients’ disease category as mild, moderate, severe & critical was note. Data was analyzed using SPSS-26. Association between age and gender between disease severity was determined by using Chi-square test. Binary logistic regression was applied to find out the effect of disease severity on serum calcium levels. P-value less than 0.05 were considered to be significant. Results: 555 patients were enrolled in the current study. The mean ages of patients were 38.34+14.86. There were 300(54.1) male and 255(45.9) female, the severity of the disease shows that the majority 490(88.3%) of the patients had mild disease and 65(11.7%) had moderate disease. The mean serum calcium level was 8.7+0.34. The majority of patients had mild disease, of which 270 were female and 220 male and 230 among 31-50 years. The results of binary logistic regression show the effect of disease severity (Mild, Moderate) on calcium, age and gender. It was reported that only serum calcium, male gender and age category 30-50 years were a significant predictor of disease severity. Conclusion: It was concluded from current study that majority of patients have mild disease severity and patients have normal serum calcium. The disease severity has no significant impact on the calcium levels as the majority of patient has mild disease. Keywords: COVID-19, Disease Severity, Hypocalcemia